Factors Affecting the Occurrence of Low Birth Weight Babies at RSKDIA Siti Fatimah Makassar in 2024 - Sutrani Syarif; Selviana Selviana; Khaerunnisa Khaerunnisa (International Journal of Health and Medicine, 2024)
Neonatal mortality consists of early neonatal death and late neonatal death. Neonatal mortality rate is the number of neonatal deaths per 1,000 live births. Low Birth Weight is one of the risk factors that contributes to infant mortality, especially during the neonatal period. This study aims to determine the factors that influence the incidence of low birth weight babies at RSKDIA Siti Fatimah Makassar in 2024. This study is analytical with a case control approach used to determine the influence between independent variables and dependent variables. The type of research is retrospective which tries to look back. This means collecting data starting from the effects or consequences that have occurred. Then from these effects the causes or variables that influence these consequences are traced. The population in this study were all babies born in January-June 2018, totaling 759 babies. The sample in this study were babies born in the delivery room of RSKDIA Siti Fatimah Makassar in 2024 with a birth weight of > 2500 grams. Based on the research results, a p value of 0.002 was obtained, thus it can be concluded that this figure means that there is an influence of maternal age on the incidence of LBW, and the p value ρ = 0.001 means that H0 is rejected, meaning that there is an influence between nutritional status and the incidence of Low Birth Weight.